2017
DOI: 10.1093/jcbiol/rux051
|View full text |Cite
|
Sign up to set email alerts
|

Density and gender segregation effects in the culture of the caridean ornamental red cherry shrimp Neocaridina davidi Bouvier, 1904 (Caridea: Atyidae)

Abstract: The effect of density on growth, sex ratio, survival, and biochemical composition of the red cherry shrimp, Neocaridina davidi Bouvier, 1904, was studied to determine optimum rearing conditions in this ornamental species. It was tested whether gender segregation affected growth and survival of the species. To test the effect of density (Experiment 1), hatched juvenile shrimp were kept at three different densities: 2.5, 5, and 10 individuals l-1 (D 2.5 , D 5 and D 10 , respectively). To test the effect of gende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 54 publications
2
17
0
Order By: Relevance
“…Offspring weight and length increment of N. davidi for the period 30-60 days was significantly different for either males or females offspring. It was previously reported for N. davidi an increment in females' growth rate in this period with respect to males, related to the differential growth at sexual maturity (Vazquez, Delevati Colpo, Sganga & López Greco, 2017), which could account for the differences observed in this study. Weight increment for the period 0-30 days was higher in second spawnings as compared to first ones.…”
Section: Discussionsupporting
confidence: 56%
“…Offspring weight and length increment of N. davidi for the period 30-60 days was significantly different for either males or females offspring. It was previously reported for N. davidi an increment in females' growth rate in this period with respect to males, related to the differential growth at sexual maturity (Vazquez, Delevati Colpo, Sganga & López Greco, 2017), which could account for the differences observed in this study. Weight increment for the period 0-30 days was higher in second spawnings as compared to first ones.…”
Section: Discussionsupporting
confidence: 56%
“…Among infected shrimp, females more likely presented damages in the cuticle, suggesting that the activity of S. japonica might be higher on them than on males, what is supported also by the presence of eggs only on females. This is most likely a result of more surface available to attach on females which grow bigger than males (Vazquez et al, 2017), what can also be observed in quantity of vorticellids, which was also lower in males. On the other hand, females are often characterised with body covered by more intense pigmentation (Tomas et al, 2019), which probably creates favourable shelter conditions for scutariellids hiding in host gill chambers.…”
Section: Resultsmentioning
confidence: 90%
“…This small caridean species is native to Asian lakes and streams (Cai, 1996), where temperatures range from 6 to 8°C in winter and nearly 30ºC in summer (Klotz et al, 2013). Several studies have demonstrated how easily this species can be cultured and maintained under laboratory conditions, due to its natural hardness to starvation (Pantaleão et al., 2015) and high tolerance to a condition of conspecific density (Vazquez, Delevati Colpo, Sganga, & López Greco, 2017). Moreover, female reaches sexual maturity approximately 50 days after hatching at 28ºC (Tropea, Stumpf, & López Greco, 2015) and displays a short life cycle with direct development, producing several successive spawnings with the same offspring quality (Marciano, Tropea, & López Greco, 2018; Sganga, Tropea, Valdora, Statti, & López Greco, 2018; Tropea & López Greco, 2015).…”
Section: Introductionmentioning
confidence: 99%